1993
DOI: 10.1111/j.1365-2265.1993.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone regulation by sex steroids in men with germinal and Leydig cell tumours

Abstract: In patients with hCG-secreting germ cell tumours complete suppression of plasma LH and FSH with increased plasma concentrations of both testosterone and oestradiol are often discovered. No such gonadotrophin suppression is found in patients with Leydig cell tumours, but the negative correlation observed between plasma testosterone and oestradiol in these patients suggests a weak negative feedback effect of oestradiol on LH secretion, which cannot be demonstrated by basal LH measurements in plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…They are consistent with data already obtained in men (Bagatell et al, 1994;Kuhn et al, 1994). It was previously suggested that androgens and oestrogens could act synergistically on gonadotrophin secretion (Handa et al, 1987;Roselli, 1991) and that the inhibitory effects of both steroids are required to obtain a complete suppression of gonadotrophin release in mammals or in man (Korach & Muldoon, 1974;Sawin et al, 1978;Winters et al, 1979;Spijkstra et al, 1988;Reznik et al, 1993). Thus, it might be hypothesized that the absence of suppressive effect of DHT upon GnRH-stimulated LH secretion could be because of the lack of sufficient amounts of endogenous E2.…”
Section: Discussionsupporting
confidence: 91%
“…They are consistent with data already obtained in men (Bagatell et al, 1994;Kuhn et al, 1994). It was previously suggested that androgens and oestrogens could act synergistically on gonadotrophin secretion (Handa et al, 1987;Roselli, 1991) and that the inhibitory effects of both steroids are required to obtain a complete suppression of gonadotrophin release in mammals or in man (Korach & Muldoon, 1974;Sawin et al, 1978;Winters et al, 1979;Spijkstra et al, 1988;Reznik et al, 1993). Thus, it might be hypothesized that the absence of suppressive effect of DHT upon GnRH-stimulated LH secretion could be because of the lack of sufficient amounts of endogenous E2.…”
Section: Discussionsupporting
confidence: 91%
“…Both androgens and oestrogens can act at the pituitary level. As suggested previously in hCG-secreting tumours, it is possible that, at a plasma E2 level similar to that observed in LCT, only a combined oversecretion of both testosterone and E2 can lead to complete suppression of gonadotrophin secretion (34). The frequency of spontaneous LH pulses reflects endogenous GnRH secretion (28,35,36).…”
Section: Discussionmentioning
confidence: 51%
“…Group I included 42 male partners (aged [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] years) of infertile couples. They were taking no medication and did not have any history of disease.…”
Section: Subjects Studiedmentioning
confidence: 99%
“…There have been reported cases of Leydig cell tumor which demonstrated only an increase of serum E2 and suppression of serum testosterone as a consequence of increased aromatase activity in tumoral Leydig cells [33]. The direct inhibitory action of elevated E2 on the enzymes involved in steroidogenesis and the negative feedback action on luteinizing hormone secretion of the E2 possibly caused the suppression of serum testosterone [34]. Due to the significant increase in weight of the patient, in our case hormonal changes were rather considered a consequence of aromatization in adipose tissue of testosterone to estradiol and gynecomastia as a consequence of increased levels of estradiol and change of estrogen/androgen ratio.…”
Section: Discussionmentioning
confidence: 99%